Analysis of Language Errors in the “Larise” Magazine Article at SMP Negeri 8 Surakarta - Dea Rahmanita Ayuningtyas; Lailatul Karimah; Silvi Intan Cahyaningsih; Chafit Ulya (research, training and philanthropy institution Natural Aceh, 2022)
This study aims to analyze language errors and their interpretations at the level of syntax, morphology, and Indonesian Spelling System as well as to increase knowledge and insight about how to write properly and correctly according to the language rules that have been regulated in the KBBI and PUEBI. This research uses descriptive qualitative research method. The data in this study are in the form of words (not numbers) sourced from Larise magazine in an article entitled